The integer roots of the equation x 2 + a x + b = 0 are a and b .
What is the sum of all possible values of the expression a + a b + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Your solution and answer are incorrect. Please fix your problem.
Log in to reply
Please ellaborate why.
Log in to reply
Have you read my report?
Log in to reply
@Sharky Kesa – Oh, sorry. The report didn't post. :P
Now it's been posted, I recommend you read it.
Shouldn't you tweak your solution so people don't keep falling in the same bear trap and answering correctly using an incorrect solution?
I believe the answer to be correct. At least, that's what I got. Ed Gray
Log in to reply
The answer is correct, but for the wrong reasons.
Here is my proof, as well as links to the same problem, with different answers:
Links to the same problem: Just apply Vieta's and Troll Quadratic
Let f ( x ) = x 2 + a x + b . We have
f ( a ) f ( b ) ⇒ b ⇒ ⇒ = 2 a 2 + b = b 2 + a b + b = − 2 a 2 and b ( b + a + 1 ) − 2 a 2 ( − 2 a 2 + a + 1 ) 2 a 2 ( a − 1 ) ( 2 a + 1 ) = 0 = 0 = 0 = 0 = 0
Thus, we have 3 solutions for a , which are a = − 2 1 , 0 , 1 . From this, we get all solutions are
( a , b ) = ( − 2 1 , − 2 1 ) , ( 0 , 0 ) , ( 1 , − 2 )
However, we must have these roots to be integers, so the a = b = − 2 1 case is nulled, leaving us with an answer of − 3 .
No ur wrong, brazilian answer is correct, u think u r too smart but u cant be
Log in to reply
I'm sorry if you don't understand the flaw in Guilherme's solution. Vieta's doesn't always work, and he has already accepted he made a flaw. The method I have shown is the correct version.
U have a far too long approach to a simple problem
Log in to reply
I'm sorry if you don't understand the flaw in Guilherme's solution. Vieta's doesn't always work, and he has already accepted he made a flaw. The method I have shown is the correct version.
x 2 + a x + b ≡ ( x − a ) ( x − b ) = x 2 + ( − a − b ) x + a b
therefore, a = − a − b and b = a b form these two equation , ( a , b ) = ( 0 , 0 ) or, ( a , b ) = ( 1 , − 2 )
∑ ( a + a b + b ) = ( 0 + 0 + 0 ) + ( 1 + 1 × ( − 2 ) + ( − 2 ) ) = − 3
Problem Loading...
Note Loading...
Set Loading...
From Vieta's Formulas, − a = a + b and b = a b . We quickly get that either b = 0 ⇒ a = 0 or a = 1 ⇒ b = − 2 .
This means that the sum of a + a b + b is 0 + 0 + 0 + 1 − 2 − 2 = − 3 .